COMPARATIVE ANALYSIS OF THE COMPLETE CHLOROPLAST GENOME OF THREE PROSOPIS SPECIES IN JORDAN - Hamad Adel Alkhatatbeh; Khaleel I Jawasreh; Maher J. Tadros (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Worldwide, Prosopis Genus is widely spread and well known to be of high tolerance to harsh conditions. The P. juliflora and P. cineraria species were introduced to the Mediterranean, while P. farcta is a native one. The genomic structure of the chloroplast of P. juliflora, P. cineraria and P. farcta were targeted in this study. The chloroplast DNA samples were sequenced by genetic analyzer sequencer “Ion S5™ System. The results indicated the size of the genome to be ranged between 162900 bp in P. farcta and 163667 bp in P. cineraria. The full chloroplast of P. juliflora and P. cineraria genome were reported for the first time nationally in Jordan, while globally P. farcta was the first to be analyzed genetically. The present study offers an important portfolio of Prosopis species chloroplast genome analyses, this could help with identification of species and speed up biological and genetic diversity researches.